2007
DOI: 10.1097/01.ogx.0000259176.03156.2b
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Blood Coagulation Factor XIII Deficiency and Successful Deliveries: A Review of the Literature

Abstract: Congenital deficiency of blood coagulation factor XIII is an uncommon, inherited disorder characterized by hemorrhagic diathesis, habitual abortions and defective wound healing. We analyzed 8 reported successful pregnancies in women with a congenital deficiency of A-subunit of factor XIII (XIIIA), in which the plasma level of maternal factor XIIIA and/or the precise replacement therapies are described. Because decidual bleeding usually begins from 5 to 6 weeks' gestation and, without replacement therapy, spont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
59
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 11 publications
0
59
0
2
Order By: Relevance
“…In patients with known congenital FXIII deficiency, replacement therapy throughout pregnancy results in successful outcomes [15][16][17]. Different regimens of prophylaxis have been used in different countries [15,18], but there is no validated recommendation regarding the optimal dose of FXIII during pregnancy. In this patient, FXIII 20 IU/kg given every 3 weeks prevented bleeding and miscarriage, but it is important to note that a shortened and dilated cervix was detected early in the pregnancy.…”
Section: Resultsmentioning
confidence: 99%
“…In patients with known congenital FXIII deficiency, replacement therapy throughout pregnancy results in successful outcomes [15][16][17]. Different regimens of prophylaxis have been used in different countries [15,18], but there is no validated recommendation regarding the optimal dose of FXIII during pregnancy. In this patient, FXIII 20 IU/kg given every 3 weeks prevented bleeding and miscarriage, but it is important to note that a shortened and dilated cervix was detected early in the pregnancy.…”
Section: Resultsmentioning
confidence: 99%
“…Classically considered as haemorrhagic disorder, it can result in a lifelong bleeding tendency [Kom谩romi et al, 2011] and defective wound healing and tissue repair [Inbal and Dardik, 2006]. It was recently found to be associated with chronic venous leg ulcers [Zamboni and Gemmati, 2007] and recurrent abortion [Asahina et al, 2007]. High factor XIII circulating levels can be detected among thrombophilic patients [Muszbek et al, 2010].…”
Section: Discussionmentioning
confidence: 99%
“…Limited data on prophylaxis during pregnancy are available; a plasma FXIII level above 10% seems to be sufficient for successful pregnancy. Asahina et al [9] have reported that 250 IU per week were sufficient to maintain this level in the early period of gestation, and 500 IU per week is recommended after the 23rd week of gestation. The same authors propose that plasma FXIII level should be higher than 30% during labor and a booster dose of 1000 IU is recommended before labor to prevent severe obstetrical hemorrhagic complication.…”
Section: Replacement Therapy (Prophylaxis On Demand Treatment)mentioning
confidence: 99%